Food allergens and oral immunotherapy as indicators of eosinophilic oesophagitis - Andrzej Kuźmiński; Justyna Przybyszewska; Zbigniew Bartuzi (Gastroenterology Review)
Eosinophilic esophagitis (EoE) is a chronic immune-mediated esophageal disease, clinically characterised by symptoms of esophageal dysfunction and histologically by eosinophilic infiltration of its wall. The last 3 decades have seen a sharp increase in its incidence to the point that it is called the second most common esophageal disease after reflux disease in some recent studies. The main indicators of EoE are food allergens and in recent years the extremely important role of oral immunotherapy (OIT) in the development of this disease has also been increasingly raised. To date, the appearance of EoE in the course of OIT is an absolute indication for discontinuation of this procedure; however, other therapeutic options that do not require termination of this procedure are increasingly being advocated. Unfortunately, our knowledge of EoE is full of gaps and requires numerous studies to fill in the missing elements of the pathogenesis and clinic of the described disease.